Microwave and Very High Frequency Radiations of the First Narrow Initial Breakdown - Shamsul Baharin S.A.; Riduan Ahmad M.; Khaleel Al-Shaikhli T.R.; Mohammad Sabri M.H.; Al-Kahtani A.A.; Mohamad S.A.; Cooray V.; Bakar Sidik M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Clouds; Microwave sensors; Centre frequency; Cloud-to-ground flash; High frequency sensors; High-frequency pulse; High-frequency radiation; Initial breakdown; Initial breakdown pulse; Pulse ranging; Radiation pulse; Very high frequency; Microwaves